Walking the line: how young athletes balance academic studies and sport in international competition - Kristiansen, E. (Sport in Society: Cultures, Commerce, Media, Politics, 2017)
Focused on the Norwegian squad for the 2015 European Youth Olympic Festival, the aims of this study are to identify (a) the perceived role of important stakeholders such as coaches, schools, parents, federations, and the national Olympic committee for the young athletes in the weeks leading up to the festival; and (b) the young athletes` festival experiences with a focus on perceived stressors by using the transactional framework. The findings of the study revealed that pursuing a dual career is often a challenging balancing act for the young student-athletes. Additional results identified the importance of supportive parents, schools that adapt the workload for the student-athletes, and a federation that recognizes the important role of parents and schools. While the rhetoric for the festival was that it was a `learning experience` for the young athletes, the young athletes perceived the event as a serious sporting competition and were aware of factors which might cause stress and thus interfere with optimal performance. This investigation offers implications for sport management and psychology researchers gaining insight into young athletes and youth sport festivals.